Math, asked by tyson112, 1 year ago

2+4+6=19
3+6+9=43
4+6+8=53
9+5+3=?
i need full process ​

Answers

Answered by FTREpreparation
1

Answer:

68

I could have explained all day if I had the time

Step-by-step explanation:

2*4 + 2*6 - 1

= 8 + 12 - 1

= 19

3*6 + 3*9 - 2

= 18 + 27 - 2

= 43

4*6 + 4*8 - 3

= 24 + 32 - 3

= 53

So next one :

9*5 + 9*3 - 4

= 45 + 27 - 4

= 68

Answered by jinadevkv
1

2 * ( 4 + 6 ) - 1 = 2 * 10 - 1 = 20 - 1 = 19

3 * ( 6 + 9 ) - 2 = 3 * 15 - 2 = 45 - 2 = 43

4 * ( 6 + 8 ) - 3 = 4 * 14 - 3 = 56 - 3 = 53

First number is multiplied with the sum of the next two and the number 1 less than first number is subtracted from it.

9 * ( 5 + 3 ) - 8 = 9 * 8 - 8 = 72 - 8 = 64

Similar questions